Pomegranate Extracts as a Natural Denture Cleanser: A Promising Alternative to Sodium Bicarbonate for Inhibiting Candida albicans - Wijaya, Cindy Denhara; Sumitro; Annisa Rizqi Ramadhani Sitio; Fitriah Khairani Harahap (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Denture stomatitis, caused primarily by Candida albicans overgrowth, is a common oral health issue among denture wearers. Maintaining denture hygiene is crucial for prevention. This study investigated the efficacy of red pomegranate (Punica granatum L.) peel and fruit extracts as natural denture cleansers compared to sodium bicarbonate, a standard denture cleansing agent. Methods: Heat-cured acrylic resin plates were fabricated and contaminated with C. albicans. Samples were divided into four groups and soaked for 8 hours in: 75% pomegranate peel extract, 75% pomegranate fruit extract, 5% sodium bicarbonate solution (positive control), and aquadest (negative control). C. albicans colony counts were performed using the spread plate technique and colony counter. Data were analyzed using Kruskal-Wallis and Mann-Whitney tests. Results: Both pomegranate peel and fruit extracts significantly reduced C. albicans growth compared to the negative control (p<0.05). The peel extract showed comparable efficacy to sodium bicarbonate (p>0.05), while the fruit extract demonstrated slightly lower but still substantial antifungal activity. Conclusion: Red pomegranate peel and fruit extracts hold promise as natural denture cleansers for inhibiting C. albicans and potentially preventing denture stomatitis. Further research is warranted to evaluate their long-term effects on denture materials and clinical efficacy.